Case Report: Novel splicing mutations in RFX5 causing MHC class II deficiency - Chen, Shan; Xu, Yuqing; Qian, Yeqing; Li, Zhaohui; Dong, Minyue (Frontiers in Genetics, 2022)
Mutations of the Regulatory Factor X5 (RFX5) have been associated with the autosomal recessive major histocompatibility class II (MHC-II) deficiency, which is a severe immunodeficiency characterized by constitutive and interferon-gamma induced MHC II expression disorder and leads to the absence of cellular and humoral T-cell response to antigen challenge. The compound heterozygous splicing mutations of RFX5: c.353+6T>G (maternally inherited) and c.757+1G>A (paternally inherited) were identified in an infant diagnosed severe immunodeficiency. The mutation c.757+1G>A was classified as likely pathogenic while c.353+6T>G was classified as the variant of uncertain significance according to American College of Medical Genetics and Genomics (ACMG). To investigate the pathogenicity of RFX5: c.353+6T>G, reverse transcription PCR (RT-PCR) was conducted with the mother’s peripheral blood. An insertion of 191-bp intronic sequence (intron 6) was found in the transcripts, and this resulted in a frameshift and premature truncation of the protein, especially reduced the DNA-binding domain (DBD) of the RFX5 protein. Our data expanded the spectrum of pathogenic mutations in MHC-II deficiency and put new insights into the genetic counseling, prenatal diagnosis and preimplantation genetic testing (PGT) for the disease.